Music for Hospitalized Children in Service-Learning: Academic and Personal Implications for Teachers in Training - García-Gil, Desirée; Cuervo, Laura; Bonastre, Carolina; Camilli, Celia (Harmonia: Journal of Arts Research and Education, 2024)
Service-learning methodology seeks to achieve a balance between academic learning and the application of the acquired knowledge for the benefit of the community. Our study aims to assess the academic and personal development of the students who participated in the educational experience and identify the benefits it brought to the attended children. The total of 73 participants involved: a) university students of a faculty of education, b) hospitalized children and their families, c) a healthcare worker, and d) several volunteers. We conducted a case study featuring qualitative analysis (based on discussion groups, interviews, and daily narratives), analysis of co-occurrence, and data triangulation. The categories we obtained were related to learning achieved by university students, their personal growth, and the impact of hospital service on the different agents who participated in the experience. Findings suggest that service-learning, along with the positive emotional impact of experiential music learning, was associated with student progress in teacher training and personal development.